Efficiency and Accessibility of Sharia Home Financing for Millennials: A Study of BSI's Griya Si Muda Program vs BTN iB Property - Fatkhurrozi, Tanto; Mugiyati (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2024)
Purpose – The study aims to explore how sharia-compliant home financing programs bridge affordability, Islamic values, and cultural traditions to meet millennial housing needs in Indonesia Method – Employing a qualitative approach with a literature study method, the research compares financing schemes, requirements, and benefits offered by Bank Syariah Indonesia (BSI) and Bank Tabungan Negara (BTN) Syariah. Findings –. Findings reveal that both programs integrate Islamic principles with modern financial practices, offering innovative solutions for millennials to achieve homeownership. BSI’s "Griya Si Muda" focuses on flexibility and affordability with fixed installments, while BTN’s "Properti iB" combines Murabahah and Musyarakah Mutanaqisah contracts for joint ownership, emphasizing long-term equity. Practical implications highlight the importance of leveraging digital platforms to enhance accessibility and cultural alignment. This study provides original insights into the role of Islamic finance in fostering sustainable housing solutions tailored to millennial preferences and socio-religious contexts. Practical implications – That millennials seeking home financing can choose a program based on their specific needs: BSI Griya Si Muda is suitable for workers with a fixed income who prioritize ease of application, certainty of installments, and a large ceiling, while BTN iB is more suitable for those who require age flexibility, self-employment, or gradual ownership options. Prospective customers should consider their financial profile, long-term plans, and financing scheme preferences before making a decision. Originality/value – a unique comparative analysis that provides guidance for millennials in choosing Islamic home financing according to their needs as well as recommendations for the development of Islamic banking products.